MYB-NFIB Translocation by FISH in Adenoid Cystic Carcinoma of the Head and Neck in Nigerian Patients: A Preliminary Report - Owosho, Adepitan A. (Head Neck Pathol, 2020)
Adenoid cystic carcinoma (AdCC) is a relatively rare malignancy of head and neck sites such as the salivary glands, lacrimal gland, sinonasal region, and pharynx and may arise in other exocrine glands. The oncologic event in AdCC is the translocation between MYB proto-oncogene transcription factor (MYB) and nuclear factor I/B (NFIB) resulting in t(6;9)(q22-23;p23-24). We carried out a preliminary evaluation of MYB-NFIB translocation by fluorescence in-situ hybridization on seven archived formalin-fixed paraffin-embedded tissues of AdCC of Nigerian patients and its clinicopathologic features. Only 3 of the 7 cases were successfully hybridized, all featuring MYB-NFIB translocations with a range of 14.7–83.3% of translocated cells in 60 cells examined. The 3 translocation positive cases were located in the maxillary sinus, buccal mucosa and parotid. Their morphologic appearances were cribriform-solid (1) & cribriform (2) and classified as grades III (1) & I (2), respectively. These patients may potentially benefit from MYB-targeted anti-neoplastic therapy.